A Cristologia Angelomórfica Joanina: Uma análise da narrativa da ascensão de Jesus em João 20,11-18. - Brito, Marco Aurélio de (2018)
Our research has born from the aim to analyze the presence of the angels in the tomb and the transcendent image that they evoke. In this matter, we have, in the first place, studied the angelic beings waiting the ascension of the Lord in the Gospel of John. This analysis showed to us the strength connection with the celestial ascension destined to humans in the Ancient World context, present on the Hebrew Scripture, the Literature from the Second Temple Period, and the Dead Sea Scrolls. So, we interpret those narratives comparing it with the Johanine high-descending Christology. Secondly, we dialogue with the terms that reveals the authority of the person of Jesus, showing how these terms were decisive to indicate his crescent authority and divination in the context of the first century Judaism, in against other important personalities of the time. In the third place, we made an exploratory research, in an dialectical process, comparing angelical beings, divinized humans, patriarchs and priests, with the literary image of Jesus in the Fourth Gospel. For that matter we argued that the loving disciple tried to construct his master filled with divine glory. In the end, we tried to interpret the account accordingly the popular imagery, where the phantasmagoric literature helped us to comprehend the Johanine account and the appearance of Jesus after his resurrection, where the afraid and hidden disciples don’t scare with the appearance of the master, even with the doors closed. We also, tried to understand every literary constructions that have some connection or that share the same semantic field of the work. Our objective is to demonstrate that the Johanine community understand itself as the true group that received the revelation of the message of the Christ, and that all those discussions presented in the work tried to exalt their master, demystifying another alleged deities. In conclusion, we argue that the ascending theological process of the Christ in the community, his Christology and the angelomorphic relations mirrored important figures of the History of Israel and, in the same time, exalted and glorified the master with the symbols showed in the text, as the Logos, the Temple, the Son of God, and others.